Beauty, bravery and courage. The young hero in “Teseide” and “Peregrinaggio di Rinaldo” by Danese Cataneo (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
This paper aims to investigate the figure of the young hero in the epic poems Teseide and Peregrinaggio di Rinaldo. Their author, the sculptor and poet Danese Cataneo (1508-1572), is known for L’Amor di Marfisa (1562), a poem that influenced Tasso’s poetry, as has been highlighted in many studies. The poems are transmitted in lacunose condition in manuscript Chig. I.VI.238 of the Vatican Library. They do, however, offer an interesting stimulus for reflection about the phenomenon of young epic heroes, since they present original stylistic and narrative solutions in the construction of their heroes’ childhood. In this article, the theme of the young hero in these poems is examined by addressing the birth of Theseus and his epiphanic childhood; the analogy between the education of the young hero and the education of the perfect prince and the ideal courtier; the “Bildungsroman” of the young Ruggiero (Rinaldo’s nephew), and finally the important moral purposes of the works.
Keywords: Italian Renaissance, Epic poetry, Theseus, Renaud de Montauban, Epic hero; Italian Renaissance; Epic poetry; Theseus; Renaud de Montauban; Epic hero